PSYCHOLOGICAL STRESS AND THE DRUZE TEACHERS' SELF-EFFICACY IN AN ONLINE LEARNING ENVIRONMENT DURING COVID- 19 IN ISRAEL - Haj, Maysaa (E-Journal VFU, 2025)
This qualitative study aimed to examine the influence of psychological pressures on the self-efficacy of Druze educators and to elucidate the correlation between these factors within the framework of the virtual learning environment. It used a structured interview method to collect data from 12 interviewees ( principals and teachers) from Druze school. Braun and Clarke’s thematic approach (2006) was used to analyze the data The findings of this study were : (i) The technical and psychological pressures reduced the efficiency of teachers in distance education.(ii) Poor interaction with students and people with special needs increased frustration and stress. (iii) Some teachers have used coping strategies, but the need for professional training and psychological support is still urgent to enhance performance. This study recommended the following: (i) Improve the technical infrastructure and provide the internet and suitable devices with fast technical support. (ii) Preparing practical training programs for teachers on e -learning and dealing with special categories. (iii) Providing psychological and professional support through counseling programs and experience exchange spaces to raise self-efficacy and reduce stress.
Keywords: COVID-19; Druzi teachers; online learning; psychological stress; self-efficacy